Assessing the Diagnostic Precision of Abdominal Ultrasonography and the Alvarado Score for Acute Appendicitis - Mohammed Hussain Hashlan, Taghreed Ahmed Alsaleh, Wejdan Nasser Almaqbul, Sawsan Fawzi Sabiq, Alaa Alduraibi, Taghreed Hussain Balhareth, Mohammed Ghanem Ghannam Alsaedi; Sager Imbarak Hamdan Alghamdi, Mohammed Fagihi, Ali Abdullah Ahmed Aseeri (Journal of International Crisis and Risk Communication Research, 2024)
Background: Acute appendicitis is a common surgical emergency with a lifetime risk of 7–8%. However, its diagnosis remains challenging due to symptom overlap with other abdominal conditions. Clinical tools like the Alvarado score and imaging methods such as abdominal ultrasonography (US) are often used to improve diagnostic accuracy. This study aims to evaluate the diagnostic performance of the Alvarado score and abdominal US for diagnosing acute appendicitis. Methods: This study was conducted including 200 patients aged 13 years and older who presented with acute abdominal pain and were suspected of having acute appendicitis. The Alvarado score and abdominal US were used to assess diagnostic accuracy, with histopathological examination serving as the gold standard for confirmed diagnoses. Diagnostic metrics such as sensitivity, specificity, positive predictive value (PPV), negative predictive value (NPV), and area under the receiver operating characteristic (ROC) curve were calculated. Results: The Alvarado score demonstrated high sensitivity (94.62%) and specificity (87.80%), with a positive predictive value (PPV) of 96.09% and a negative predictive value (NPV) of 83.72%. Abdominal US showed a sensitivity of 98.46% and specificity of 82.93%, with a PPV of 94.81% and an NPV of 94.44%. The area under the ROC curve (AUC) for both the Alvarado score and abdominal US was 0.938 and 0.907, respectively. Conclusion: Both the Alvarado score and abdominal ultrasound demonstrated high diagnostic accuracy in diagnosing acute appendicitis. These tools are particularly useful in resource-constrained settings, helping to minimize unnecessary surgical procedures and reducing healthcare costs.